Empowering Health Cadres to Improve Primary Healthcare Access and Quality: A Case Study In Jekek Village, Nganjuk, Indonesia - Susanti, Titin; Laili Wulandari; Rifka Sari Pratiwi; Endah Wulan Safitri (Journal of Community Engagement in Health, 2025)
Primary health care services serve as the frontline of public health development. Health cadres play a strategic role as intermediaries between communities and health facilities, yet their capacity remains limited. This community service project aimed to analyze the impact of strengthening cadres’ roles through structured training on knowledge, skills, attitudes, and self-efficacy in improving access to and quality of primary health care services in Jekek Village, Nganjuk Regency. The study applied a Participatory Action Research (PAR) approach involving 25 posyandu cadres. The evaluation showed a 25% increase in cadres’ knowledge based on pre- and post-test results. Community participation in posyandu increased by 20%, and cadres demonstrated improved skills in health data recording and communication with residents. Furthermore, the establishment of a communication forum between cadres, the puskesmas, and the village government contributed to the sustainability of the program. The findings highlight that effective empowerment strategies include continuous training, area-based mentoring, and non-financial incentives such as social recognition and competency certification. Empowerment through a participatory approach was proven to enhance access and quality of primary health care services and strengthen community-based health systems, although limited training opportunities and logistical constraints remain challenges. Sustainable policy support is therefore needed to further strengthen cadres’ capacity in primary health care delivery.